42nd AIAA Fluid Dynamics Conference and Exhibit 2012
DOI: 10.2514/6.2012-3346
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Atmospheric Uncertainties on Long Range Propagation of Infrasounds

Abstract: The normal mode method provides a reduced basis that can decribe the long range propagation of infrasounds in the atmosphere. Using that technique, we study the infrasound signal recorded in Japan after the explosion of the first reactor of the Fukushima power plant. By applying small perturbations to the sound speed profile, we find highly sensitive structures that can radically impact the signal. Moreover, the main tendencies seem to change when considering different datasets for the meteorological profiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 5 publications
2
6
0
Order By: Relevance
“…First we show that the results of our code agree with those obtained by Bertin et al 1 when the sound speed only weakly depends on r. Next, we assess the effect of topography and streamwise atmospheric variations on the ground signals.…”
Section: Resultssupporting
confidence: 73%
See 4 more Smart Citations
“…First we show that the results of our code agree with those obtained by Bertin et al 1 when the sound speed only weakly depends on r. Next, we assess the effect of topography and streamwise atmospheric variations on the ground signals.…”
Section: Resultssupporting
confidence: 73%
“…We refer the reader to the article by Candelier et al 9, 10 for more details on this code. Interestingly, Bertin et al 1 showed that very close velocity profiles c(z) could lead to distinct arrivals. However, since the real profile is non-homogeneous from the source to the station, his results also suggest that horizontal variations of the wind must be considered when modeling the long-range propagation of impulsive sound.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations